Chemokines effect on kinases and phosphatases involved in Alzheimer’s disease pathology - Vaz, Margarida Isabel Nascimento (2019)
Alzheimer’s disease (AD) is a devastating worldwide disease and the main cause of dementia. In its pathology, are include two main hallmarks: the extracellular deposition of Aβ peptides, formed in amyloidogenic processing of APP, that aggregate into senile plaques (SP) and the intracellular formation of neurofibrillary tangles (NFT), aggregates of hyperphosphorylated tau protein. Tau hyperphosphorylation occurs due to increased kinase activity (including GSK3β and CDK5) and impaired protein phosphatase activity (PP2A, PP1 and PP2B). Neuroinflammation is a crucial event in AD pathogenesis, during which microglia and astrocytes are constitutively activated, leading to massive production of cytokines. These molecules may alter APP amyloidogenic processing, Aβ aggregation or tau phosphorylation. Among cytokines, chemokines seem to have an important role in AD progression. In the present work, chemokines interleukin 8 (IL-8) and monocyte chemoattractant protein 1 (MCP-1) impact on tau phosphorylation was addressed. Additionally, the effect of these chemokines on kinases (GSK3β and CDK5) and phosphatase (PP1 and PP2A), important in this process, was evaluated. For both chemokines, a significant increase in ptau S396 levels was observed at longer incubation periods and higher chemokines concentration. Further, results regarding GSK3β support that this is not the main involved kinase in this process. However, preliminary results suggest that CDK5, PP1 and PP2A can have a role in tau increased phosphorylation, promoted by chemokines. This work supports the involvement of chemokines on tau hyperphosphorylation and potentially in NFT formation, that consequently result in AD neurodegeneration. At a disease view, this thesis allowed a better understanding of molecular mechanisms that underling the disease pathology, highlighting the role of inflammation in this process.